2023
DOI: 10.1021/acsenergylett.3c00685
|View full text |Cite
|
Sign up to set email alerts
|

Direct Observation of Intragrain Defect Elimination in FAPbI3 Perovskite Solar Cells by Two-Dimensional PEA2PbI4

Abstract: Two-dimensional perovskites have widely been used to improve the efficiency and stability of perovskite solar cells and are generally believed to passivate defects at the grain boundaries of threedimensional perovskites. Herein, we studied introducing various combinations of two-dimensional phenyl ethylammonium lead iodide (PEA 2 PbI 4 ) and methylammonium chloride (MACl) to the formamidinium lead iodide (FAPbI 3 ) precursor solution. Ultralow dose selected area electron diffraction studies prove that the high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 63 publications
2
5
0
Order By: Relevance
“…However, there are fewer defects at GIs, so there is no significant V OC drop, and even a certain increase in V OC with the continuous time, which may be attributed to the formation of the bromine-rich phase here . Previous reports have shown that 2D perovskites are mainly distributed at the GBs. ,,, Similarly, our results also show that the FPEAI treatment modifies the electronic properties of the GBs, resulting in higher CPD and significantly higher V OC and better V OC stability under continuous light at GBs compared to the control samples (Supplementary Note 3).…”
supporting
confidence: 70%
See 4 more Smart Citations
“…However, there are fewer defects at GIs, so there is no significant V OC drop, and even a certain increase in V OC with the continuous time, which may be attributed to the formation of the bromine-rich phase here . Previous reports have shown that 2D perovskites are mainly distributed at the GBs. ,,, Similarly, our results also show that the FPEAI treatment modifies the electronic properties of the GBs, resulting in higher CPD and significantly higher V OC and better V OC stability under continuous light at GBs compared to the control samples (Supplementary Note 3).…”
supporting
confidence: 70%
“…13 Previous reports have shown that 2D perovskites are mainly distributed at the GBs. 28,29,32,61 Similarly, our results also show that the FPEAI treatment modifies the electronic properties of the GBs, resulting in higher CPD and significantly higher V OC and better V OC stability under continuous light at GBs compared to the control samples (Supplementary Note 3).…”
supporting
confidence: 62%
See 3 more Smart Citations